Kajian penerapan bioteknologi pengolahan kulit untuk mengurangi limbah - Prayitno Prayitno (Majalah Kulit, Karet, dan Plastik, 2010)
In its wider scope, biotechnology has been used in the tanning industry for several years, since the inception of enzyme utilization. Enzyme in leather processing can be successfully applied at the several stage of processes. At the soaking, enzyme was able to decrease soaking time from 7 hours to 4 hours for salted raw stock and from 24 hours to 10 hours for dried raw stock. At the liming and unhairing processes, however enzyme can be recover a good quality of hair with a good saleable value, recution of sodium sulfide to minimize the waste, the quality of tanned leather will increase, by using 3 % of the enzyme concentration moreover the tensile strength increased from 138,35 kg/cm2 to 209.50 kg/ cm2,while elongation at break degrease from 69.91% to 62.54%. at the bating process, the proteolitic enzyme was the only one substance and it can’t be substituted by other chemicals. At the degreasing process, the use of lipase enzyme will improve the quality of waste effluent, it was due to the application of fat solvent on contional method of tanning. The use 0.02% concentration of collagenase enzyme in vegetable tanning will increase the tanning’s substance absorption efficiency by 98%. Whereas at the waste treatment, the acidophilic fungi might absorb chromium that was liberated from the re-tanning process with 95% affectivity. Immobilized cells were also possible to be applied in effluent waste treatment of leather industry.  Keyword : biotechnology, enzyme, tanning, waste Dalam lingkup yang lebih luas, bioteknologi telah diterapkan dalam industry kulit bertahun-tahun sejak diperkenalkannya enzim. Pada proses penyamakan kulit penggunaan enzim cukup sukses pada beberapa tahapan proses. Pada proses perendaman (soaking) dapat mempercepat waktu perendaman dari 7 jam menjadi 4 jam untuk kulit awet garam dan dari 24 jam menjadi 10 jam untuk kulit awet kering. Pada proses pengapuran dan penghilangan bulu (liming dan unhairing) akan menghasilkan bulu kualitas baik yang mempunyai nilai jual dan mengurangi pengunaan garam sulfide sehingga dapat mengurangi cemaran. Kulit samak yang dihasilkan meningkat kualitas pada penggunaan 3 % ensim, sementara kuat tarik meningkat dari 138,35 kg/cm2 menjadi 209,50 kg/cm2, namun kemuluran turun dari 69,91% menjadi 62,54%. Pada proses pengkikisan protein (bating), enzim protease merupakan satu-satunya bahan bating dan tidak bias digantikan oleh kimia lain. Pada proses penghilangan lemak (degreasing) maka penggunaan enzim lipase dapat mengurangi cemaran akibat bahan pelarut lemak yang digunakan pada cara konvensional. Penggunaan enzim kolagenase sebesar 0,02 % pada proses penyamakan dengan pada cara konvensional. Penggunaan enzim kolagenase sebesar 0,02% pada proses penyamakan dengan samak nabati telah meningkatkan efisiensi penyerapan bahan penyamak sampai 98%. Sedangkan penanganan limbah dengan bioteknologi mengurangi kromium pada proses penyamakan ulang menggunakan jamur asidophilik yang efektifitas mencapai 95%. Penggunaan immobilisasi sel memungkinkan untuk diterapkan pada penanganan limbah industry penyamaan kulit. Kata Kunci : bioteknologi, ensim, penyamakan, limbah.